The terminal crest: morphological features relevant to electrophysiology. Issue 4 (1st October 2002) - Sánchez-Quintana, D; Anderson, R H; Cabrera, J A; Climent, V; Martin, R; Farré, J; Ho, S Y
Abstract : Objective: To investigate the detailed anatomy of the terminal crest (crista terminalis) and its junctional regions with the pectinate muscles and intercaval area to provide the yardstick for structural normality. Design: 97 human necropsy hearts were studied from patients who were not known to have medical histories of atrial arrhythmias. The dimensions of the terminal crest were measured in width and thickness from epicardium to endocardium, at the four points known to be chosen as sites of ablation. Results: The pectinate muscles originating from the crest and extending along the wall of the appendage towards the vestibule of the tricuspid valve had a non-uniform trabecular pattern in 80% of hearts. Fine structure of the terminal crest studied using light and scanning electron microscopy consisted of much thicker and more numerous fibrous sheaths of endomysium with increasing age of the patient. 36 specimens of 45 (80%) specimens studied by electron microscopy had a predominantly uniform longitudinal arrangement of myocardial fibres within the terminal crest. In contrast, in all specimens, the junctional areas of the terminal crest with the pectinate muscles and with the intercaval area had crossing and non-uniform architecture of myofibres. Conclusions: The normal anatomy of the muscle fibres and connective tissue in the junctional area of the terminal crest/pectinate muscles and terminal crest/intercaval bundle favours non-uniform anisotropic properties.